2022
DOI: 10.1111/eje.12763
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and knowledge of dental radiography amongst students of dentistry and related fields

Abstract: Objectives This study aimed to evaluate the level of knowledge and attitude towards quality control in dental radiography amongst students of dentistry, allied dental sciences and radiologic technology programmes. Methods A cross‐sectional survey was conducted using self‐administered questionnaire on a convenience sample of 580 students from three universities in Jordan. The questionnaire was divided into sections that include personal sociodemographic variables, knowledge about quality assurance in dental rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Study results revealed that most dentists were aware of radiation hazards and protection. 1,2 Our results are comparable to studies conducted previously like a study done in 2020 by Khamtuikrua C, et al, 3 and Mahasneh AM, et al, 4 in the year 2022. Dental radiography is considered safe during pregnancy if protective measures have been provided such as thyroid collar, Lead apron, and use of highspeed E films.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Study results revealed that most dentists were aware of radiation hazards and protection. 1,2 Our results are comparable to studies conducted previously like a study done in 2020 by Khamtuikrua C, et al, 3 and Mahasneh AM, et al, 4 in the year 2022. Dental radiography is considered safe during pregnancy if protective measures have been provided such as thyroid collar, Lead apron, and use of highspeed E films.…”
Section: Discussionsupporting
confidence: 90%
“…The literature review reveals that not only do dental students and dentists lack knowledge regarding radiation protection and proper techniques of radiograph taking but they are not aware of advising proper radiographs for different conditions. 4,5 Studies regarding radiation hazards are widely available but no study assessing basic radiographic knowledge and indications of different radiographs has been conducted so far nationally. So, the general knowledge about dental radiology is questionable and our study aimed to assess general awareness about the said subject as this field needs a lot of improvement to provide quality services in a clinical or hospital setup.…”
Section: Introductionmentioning
confidence: 99%